A rare case report of psoas abscess in pregnancy in a tertiary centre - Chavan, Niranjan N.; Ammara, Umme; Dias, Zaneta; Boob, Manan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
A psoas abscess in pregnancy is a relatively uncommon condition with nonspecific signs and symptoms. It may lead to serious complications if not diagnosed and treated promptly. Although spinal tuberculosis affects nearly half of skeletal tuberculosis patients, psoas abscess develops in only 5% of spinal tuberculosis cases. A clinical history and examination are used to make a diagnosis, which is then confirmed by microbiology and radiological findings. Here is an interesting case report on psoas abscess in pregnancy managed by pigtail catheter insertion and drainage.